2018
DOI: 10.1002/14651858.cd010612.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Timing of renal replacement therapy initiation for acute kidney injury

Abstract: Background Acute kidney injury (AKI) is a common condition among patients in intensive care units (ICUs), and is associated with high death. Renal replacement therapy (RRT) is a blood purification technique used to treat the most severe forms of AKI. The optimal time to initiate RRT so as to improve clinical outcomes remains uncertain. This review complements another Cochrane review by the same authors: Intensity of continuous renal replacement therapy for acute kidney injury. Objectives To assess the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 169 publications
2
30
1
4
Order By: Relevance
“…Our present review did not demonstrate a statistically significant survival benefit of early RRT initiation, which is in line with the findings of most previous reviews [5][6][7][8][9][10]. Several studies that revealed positive [13] or negative [14,29,30] effects of early RRT initiation were not included in our meta-analysis.…”
Section: Present Studysupporting
confidence: 91%
See 2 more Smart Citations
“…Our present review did not demonstrate a statistically significant survival benefit of early RRT initiation, which is in line with the findings of most previous reviews [5][6][7][8][9][10]. Several studies that revealed positive [13] or negative [14,29,30] effects of early RRT initiation were not included in our meta-analysis.…”
Section: Present Studysupporting
confidence: 91%
“…Several recent meta-analyses examined the effect of early RRT initiation on patient survival and related outcomes [5][6][7][8][9][10][11]. All but one meta-analysis [11] reported that the early initiation of RRT did not provide a survival advantage (Additional file 1: Table S7).…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The relationship between CRRT and patients' outcome varied in patients with the different disease and was effected by the modalities, anticoagulation, vascular access management, timing of initiation and intensity of CRRT. 17,20,21 To date, no specific treatment has been confirmed to be effective for COVID-19, and supportive treatment remains essential. As far as we know, the effect of CRRT on critically ill patients with COVID-19 has not been reported.…”
mentioning
confidence: 99%
“…The current evidence and KDIGO guideline support the implementation of CRRT in hemodynamically unstable patients and those with increased intracranial pressure [7]. Moreover, there is increasing evidence that CRRT is associated with a trend of short-and longterm dialysis independence [8][9][10][11]. However, there is no evidence demonstrating a mortality difference between all these modalities of RRT [8,10].…”
Section: Crrt Versus Intermittent and Extended Hdmentioning
confidence: 99%